Effects of IAAF Kid’s Athletics Programme on Psychological and Motor Abilities of Sedentary School Going Children - Abhaydev, C. S.; Bhukar, J.; Thapa, R. K. (Physical Education Theory and Methodology, 2020)
The purpose of this study was to find the effects of a 12 weeks IAAF Kid’s Athletics programme on the psychological and motor fitness abilities of sedentary school-going children. Materials and methods. The study involved 40 students (age 10 to 14 years) with no previous history of systematic training. The subjects were further sub-divided based on their age, i.e. low age (10 to 11 years) and high age (13 to 14 years), and then randomly assigned to either an experimental group (Kid’s Athletics) or a control group. The psychological variables selected were stress tolerance reactive, simple motor speed, simple reaction speed, visual perception, and focused attention, whereas motor variables selected were sit and reach test, standing broad jump, 50m sprint, T-test, and 150m sprint. Tests were conducted pre-training, mid-training, and post-training for motor variables while only pre-training and post-training tests were conducted for psychological variables. Results. The two-way mixed ANOVA revealed a significant difference in all the selected variables (motor and psychological variables) in group × time interaction (p = 0.001 to <0.001) with large effect sizes. Lager effect sizes in motor fitness variables were observed after 12 weeks (ES = 2.09 to 5.72) than 6 weeks (ES = 1.92 to 3.47) when compared to baseline in the experimental group. Conclusion. The study shows that Kid’s Athletics recommended by IAAF may be considered as an effective programme to improve psychological as well as motor abilities in sedentary school-going children.